Endotracheal tube cuff pressure changes during manual cuff pressure control manoeuvres: An in‐vitro assessment. Issue 1 (21st August 2018) - Aeppli, Norbert; Lindauer, Bastian; Steurer, Marc P.; Weiss, Markus; Dullenkopf, Alexander
Abstract : Background: Endotracheal tube (ETT) cuffs are designed to seal the lower airway for precise ventilation and to protect against ingress of pathogens from the pharyngeal space. Therefore, a minimal continuous cuff pressure must be maintained. Aim of this study was to analyse the course of cuff pressure in an in‐vitro model during manual cuff pressure control manoeuvres. Methods: An artificial trachea was intubated with an appropriately sized ETT and cuff pressure set to 20 cm H2 O. Thirty‐two experienced ICU nurses each performed six cuff pressure control manoeuvres (three times in two different ETTs) using a manual cuff pressure manometer. Course of cuff pressure from connecting the manometer to disconnecting it from the cuff pilot balloon was recorded using a pressure transducer. Results: There were 190 cuff pressure control manoeuvres suitable for analysis. In all control manoeuvres a cuff pressure below 20 cm H2 O was noted. In 20.0% of the control manoeuvres the cuff pressure dropped below 10 cm H2 O. Cuff pressure drops were mainly caused by initially connecting the manometer to the pilot balloon, less frequently by manipulating the pressure gauge of the manometer. Disconnecting the manometer after the control manoeuvre caused a cuff pressure drop in 78.1% of cases, contributing to a final cuff pressure below 20 cm H2 O in 31.3% of control manoeuvres. Conclusion: Routine manual cuff pressure control manoeuvres in ETT cuffs result in considerable cuff pressure drops. This may have an impact on silent aspiration of pharyngeal contents passing along the cuff into the lower airway.